THE CAPACITY OF ENGLISH TEACHERS FOR THE IMPLEMENTATION OF ACCELERATED CURRICULUM - Magvirah El Walidayni Kau; Otoluwa, Moon Hidayati; Ririn Djimun (Adisam Publisher, 2024)
The focus of this study is to figure out how ready English teachers are in West Popayato Subdistrict junior high schools to adopt the newly established curriculum. The method of data collection employed was interviews, with two English teachers from SMP Negeri 2 West Popayato and SMP Negeri 3 West Popayato Satap helping as participants. The interactive analysis phases of data reduction, data display, and conclusion drawing from Miles & Huberman were applied in data analysis methodologies. The findings demonstrated that English teachers were not at the point where they were ready to adopt the accelerated curriculum in their schools. The instructors brought up three points. Firstly, parents' involvement is still below the level of collaborating in tandem with teachers as resource persons. Second, to allow students to learn based on their accomplishments, teachers do not separate their classes into at least two groups that are subsequently taught by the same teacher. Third, teachers continue to employ the Ministry of Education and Culture's flow of learning objectives. Because teachers are still getting used to the accelerated curriculum, these three points are still in the early stages of implementation. Thus, according to the study's findings and the stages of the accelerated curriculum's implementation table provided by the Ministry of Education and Culture, English teachers are not yet at the point where they are prepared to implement it.